The Influence of Regional Revenue Components on Regional Capital Expenditure in Indonesia (2019–2024) - Putrianto, Felisha Masayu Duanita; Putri, Risqi Noor Hidayati (Journal of Governance, Taxation and Auditing, 2026)
The effective implementation of fiscal decentralization requires local governments to manage their budgets in a more targeted manner, particularly by prioritizing capital expenditure, wich represents long-term investment, is vital for stimulating ecenomic growinwth and elevating the standard of public service provision. This reserach investigates the degree to which regionally sourced income, the general allocation fund, the special allocation fund, and the revenue sharing fund shape the capital spending allocation decisions of local goverments across indonesia. Using a quantiative methodology, the study applies panel data regression to analyze this relationship, this research utilizes based on regional budget execution records of 34 provinces in Indonesia spanning the 2019–2024 period. The test results indicate that, collectively, tahat PAD, DAU, DAK, and DBH collectively exert a significant effect on capital expenditure. However, when examined individually, in PAD, DAU, DAK are each associated with significant growth in capital spending. This finding underscores the role of fiscal autonomy and purpose-specific transfers in promoting investment in fixed assets. Conversely, DBH exerts a significant negative influence impact on capital expenditure, suggesting that DBH contributions are more likely to be absorbed by regional operational spending, thereby reducing the capacity for physical investment. The policy implications emphasize the need for adjustments in the allocation mechanisms of DBH and for strengthening local governments' capacity to enhance PAD. This strategy is vital for optimizing fiscal resources to support sustainable infrastructure development.